Assessment of in vivo and in vitro anti-tumoral effects of Lycium barbarum extract on Ehrlich ascites tumor cells: histopathology, DNA damage and AgNOR: Anticarcinogenic effect of Lycium barbarum - Uçar, Sümeyye; Ülger, Harun; Al, Özge; Nisari, Mehtap; Şeker Karatoprak, Gökçe; Cantürk Tan, Fazile; Farooqi, Ammad Ahmad; Yılmaz, Seher (Cellular and Molecular Biology, 2024)
Natural product research has an exciting and glorious past that spans over millennia. Accordingly, natural products mediated inhibition of carcinogenesis by mechanistic modulation of deregulated signaling pathways has revolutionized the field of translational oncology. Lycium barbarum has antioxidant and anticarcinogenic effects. The antioxidant activity of the extract and its effect on Ehrlich ascites tumor (EAT) were investigated using in vivo and in vitro techniques. EAT cells were injected into Balb/C mice to create stock mice. EAT cells withdrawn from stock mice were used in equal volumes in the studies. The in vivo study consisted of control and treatment groups (200 mg/kg fractions above and below 50 kDa of extracts). The liver tissues were evaluated for histopathological (H&E), DNA damage (Comet assay), and proliferation (AgNOR staining) status. The in vitro study consisted of control and treatment groups (1500 and 2000 µg/ml of extracts). Cell viability and apoptosis were evaluated. As a result, a decrease in the adhesion of EAT cells, and decreased DNA damage were observed in mice intraperitoneally administered with the fractions of Lycium barbarum. The extracts both below and above 50 kDa increased apoptotic death in cancer cells. The extract above 50 kDa was more active than those below 50 kDa. Lycium barbarum consumption may be effectual in preventing cancer formation and slowing the progression of cancer